Classification of Balinese Traditional Clothing Using Naïve Bayes - Rinaldi, Guruh Johan; Santiyasa, I Wayan (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 9 No 4 (2021): JELIKU Volume 9 No 4, Mei 2021DO - 10.24843/JLK.2021.v09.i04.p11, 2021)
Bali is an area rich in cultural products, one of the cultural products that attracts attention is traditional Balinese clothing. Balinese traditional clothing is an important cultural product for Balinese people themselves because it is used in religious activities or traditional activities in Bali. Dataset of Balinese traditional clothing obtained as many as 26 pieces by direct survey to several places of makeup as well as from the book “ Busana Adat Bali” . Furthermore, the data will be classified using the Naive Bayes method. In two experiments, there was an equally large accuracy of 66.66% using the Naïve Bayes method.